2018
DOI: 10.1371/journal.pone.0206035
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pregnancy body mass index (BMI) and maternal gestational weight gain are positively associated with birth outcomes in rural Malawi

Abstract: BackgroundWhereas poor maternal nutritional status before and during pregnancy is widely associated with adverse birth outcomes, studies quantifying this association in low income countries are scarce. We examined whether maternal pre-pregnancy body mass index (BMI) and weight gain during pregnancy are associated with birth outcomes in rural Malawi.MethodsWe analyzed the associations between pre-pregnancy BMI and average weekly gestational weight gain (WWG) and birth outcomes [duration of gestation, birth weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 24 publications
6
39
2
Order By: Relevance
“…In the RDNS, GWG rate was not associated with gestational age at delivery. This is consistent with findings from the United States, Ireland, and Taiwan (Dahly et al, ; Huang et al, ; Sharma et al, ), but not with several other reports suggesting that low GWG is associated with prematurity (Black, Sacks, et al, ; Enomoto et al, ; Li et al, ; Shin & Song, ) or duration of gestation (Gondwe et al, ). One potential explanation for these conflicting results is that most of the studies that have shown an association failed to adjust total GWG for gestational age at last measurement or otherwise account for the duration of pregnancy by calculating GWG rate (Sharma et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the RDNS, GWG rate was not associated with gestational age at delivery. This is consistent with findings from the United States, Ireland, and Taiwan (Dahly et al, ; Huang et al, ; Sharma et al, ), but not with several other reports suggesting that low GWG is associated with prematurity (Black, Sacks, et al, ; Enomoto et al, ; Li et al, ; Shin & Song, ) or duration of gestation (Gondwe et al, ). One potential explanation for these conflicting results is that most of the studies that have shown an association failed to adjust total GWG for gestational age at last measurement or otherwise account for the duration of pregnancy by calculating GWG rate (Sharma et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…We found only two other studies in lower income countries that addressed the association between GWG and birth outcomes (Gondwe et al, 2018;Ota et al, 2011). In rural Malawi, women with low weekly weight gain were at increased risk of having infants with LBW and small head circumference (P = .024) than were those with normal weight gain (Gondwe et al, 2018). In Vietnam, GWG < 10 kg was associated with 90% greater odds of SGA than was GWG of 10-15 kg (Ota et al, 2011).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Gondwe et al in Malawi reported a higher risk of stunting at birth in infants born from underweight mothers during pregnancy as well as an association between inadequate GWG and a higher risk of LBW and SGA. 37 In our study, the infant's growth trajectory differed strongly as early as birth between infants born from mothers affected by obesity vs underweight, suggesting the effect of early maternal determinants. This observation is in line with the DOHaD concept.…”
Section: Discussionmentioning
confidence: 48%
“…In particular, in studies conducted in Sudan, Ghana, and South Africa, obesity during pregnancy was associated with macrosomia at birth. Gondwe et al in Malawi reported a higher risk of stunting at birth in infants born from underweight mothers during pregnancy as well as an association between inadequate GWG and a higher risk of LBW and SGA …”
Section: Discussionmentioning
confidence: 98%